Formation of nanowires via single particle-triggered linear polymerization of solid-state aromatic molecules. Issue 32 (29th June 2016) - Horio, Akifumi; Sakurai, Tsuneaki; Lakshmi, G. B. V. S.; Kumar Avasthi, Devesh; Sugimoto, Masaki; Yamaki, Tetsuya; Seki, Shu
Abstract : Nanowires were formed via intra-track solid-state polymerization of aromatic amines triggered by high-energy charged particles' interaction with the matter. Abstract : Nanowires occupy a prestigious place in nanoelectronics, nanomechanics, and biomimetics. Although there are notable methods to grow nanowires via self-assembly, there is a key drawback in the need to find out the specific conditions appropriate for each system. In this sense, universal techniques to fabricate such nanowires from various organic materials have been sought for the continued progress of the related research field. Here we report one of the promising and facile methodologies to quantitatively produce nanowires with controlled geometrical parameters. In this method, referred to as "Single Particle-Triggered Linear Polymerization (STLiP)", organic thin films on a supporting substrate were irradiated with high-energy charged particles, accelerated by particle accelerators. Each particle penetrates from the top of the films to the substrate while gradually releasing kinetic energy along its trajectory (ion track), generating reactive intermediates such as radical species that eventually induce propagation reactions. The resulting polymerized products were integrated into nanowires with uniform diameter and length that can be isolated via development with appropriate organic solvents. Considering the widely applicable nature of STLiP to organic materials, the present technique opens a new door for access to a number of functional nanowires and their assembly.